تأثير البيئة المحاسبية الجزائرية على بدائل القياس المحاسبي في ظل سياسات المحافظة على رأس المال - سباع،, أحمد الصالح (جامعة الوادي - University of Eloued, 2021)
هذه الدراسة إلى إظهار تأثير الجزائري البيئة المحاسبية على محيط القياس المحاسبي في ضوء سياسات الحفاظ على رأس المال ، من المشاكل التي واجهت المشاكل تطبيق بدائل القياس المحاسبي للرسائل في الدولية معايير المحاسبة الدولية IAS / IFRS in ولقياس هذا التأثير تم تصميم استبيان لجمعه معلومات من عينة الدراسة حيث 137 مؤسسة اقتصادية وممارسين المحاسبة سواء المهنيين أو المتداولين الإحصاء القياسي والدراسات مثل الانحدار الاختبارات البارامترية واللامحدارية وقد وصلت الدراسة إلى:  توجد علاقة موجبة ذات دلالة إحصائية على مستوى 0.0 = 0.05 بين تأثير المحاسبة الجزائرية البيئة وعوامل القياس على تطبيق القياس المحاسبي في الجزائر في ضوء رأس المال سياسات الحفظ ؛  توجد علاقة موجبة ذات دلالة إحصائية عند مستوى α = 0.05 بين بدائل القياس المحاسبي توزيع القوانين والتشريعات في الجزائر على تطبيق بدائل القياس المحاسبي في الجزائر. للامتثال ل مبدأ التكلفة كأساس للقياس المحاسبي نواقصها التي تعكس الحالي الحالي للمقارنة ؛ علاقة موجبة ذات دلالة إحصائية على المستوى ذات دلالة 0.05 = α بين السوق المالية في الجزائر و بدائل القياس المحاسبي على تطبيق بدائل القياس المحاسبي في الجزائر سواء أتت إلى مداخل القياس المحاسبي أو التأثير السوق المالي. أوصت الدراسة التخلص من التخلص من مشاكل التشخيص أو الرياضيات في القياس المحاسبي العمل والعمل على إيجاد عمل للعمل على العمل على مستويات عالية معايير المحاسبة الدولية إعداد التقارير المالية في الجزائر ، وخاصة في مجال إصدار لمحلية ، تليها القوانين والتشريعات التي تنظمها.This study aimes at showing demonstrate the impact of the Algerian accounting environment on alternatives to accounting measurement in light of capital conservation policies, by examining the obstacles that faced the application of accounting measurement alternatives contained in international accounting standards or international financial reporting standards IAS / IFRS in Algeria, and to measure this Impact A questionnaire was designed to collect information from the study sample and statistically treat it by (SPSS), where the study sample consisted of 137 economic institutions and practitioners of the accounting profession, whether professionals or academics, using the appropriate statistical methods for such studies as multiple regression, parametric and non-parametric tests and the study reached:  There is a positive Relationship with statistical significance at the level of significance 0.0 = 0.05 between the influence of the Algerian accounting environment and the factors of measurement on the application of accounting measurement alternatives in Algeria in light of capital preservation policies;  There is a positive relationship with statistically significant significance at the level of α = 0.05 between the alternatives of accounting measurement under the laws and legislations in Algeria on the application of alternatives to accounting measurement in Algeria. To comply with the principle of historical cost as a basis for accounting measurement, despite its deficiencies that reflect the current reality of the institution;  that there is a positive relationship with statistical significance at the level of significance 0.05 = α between the financial market in Algeria and the alternatives of the accounting measurement on the application of the alternatives to the accounting measurement in Algeria, whether it comes to the entrances to the accounting measurement or the impact of the financial market. The study recommended the need to get rid of the problems of estimation in accounting measurement through the use of statistical or mathematical methods, and work to find a mechanism of work at all levels and with high efficiency in line with international standards of accounting and international financial reporting in Algeria, especially in the area of issuing local standards, followed by laws and legislation governing It is organized.
دراسة لعينة من المؤسسات الإقتصادية
أطروحة دكتوراه تخصص تدقيق ومراقبة التسيير في العلوم اللإقتصادية و التجارية و علوم التسيير
Keywords: القياس المحاسبي ، المحاسبة الجزائرية البيئة والسياسات المحاسبية على رأس المال والمعايير المحاسبية و الإدارة الدولية لإعداد التقارير المالية IAS / IFRS ، المحاسبة المالية نظام SCF.; Alternatives to accounting measurement,The Algerian accounting environment, Capital conservation policies, Accounting standards and international financial reporting standards IAS / IFRS, The financial accounting system SCF.